Big Data Trade Survey Pricing, Trading, and Data Protection - Umbu Zogara, Lukas (Universitas Utpadaka Swastika, 2024)
In this era, Big Data is considered as the key to unlocking the growth of people's productivity in daily life. Internet usage, mobile applications and social networks, as well as the internet of things based on smart-grid and so on has an impact on the amount of data collected. The advancement of analytics data provided by machine learning and data mining technology supported by cloud computing, the resulting information will be more useful. Since the advent of Big Data, the dataset has become one type of